Novel Contributions to the Taxonomy of the Ciliates Genus Euplotes (Ciliophora, Euplotida): Redescription of Two Poorly Known Species, With a Brief Note on the Distributions of This Genus in Coastal Waters of Southern China - Liu, Weiwei; Jiang, Jiamei; Tan, Yehui; Lin, Xiaofeng (Frontiers in Marine Science, 2020)
As the typical periphytic ciliate, the genus Euplotes Ehrenberg, 1830 is highly diversified and commonly observed in marine water. In this study, the living morphology, infraciliature and silverline system of two poorly known Euplotes species, E. neapolitanusWichterman, 1964 and E. antarcticusFenchel and Lee, 1972, isolated from coastal water of southern China, were investigated. The original description of these two species were brief, and thus we provided detailed redescription based on our Chinese population. Their diagnoses were improved by adding some morphology characteristics and their detailed illustrations and photomicrographs were first supplied here. Based on the sufficient justification for identification of our population by morphology, their small subunit ribosomal RNA gene sequences which have been reported were linked to the accurate species name. Phylogenetic analyses showed that these two species cluster with their congeners which shared high morphological similarities with them. In addition, the geographic distribution of the genus Euplotes in coast of southern China was revealed, and the mangrove was considered as the ideal habitat for them by possessing the higher species richness.